Pan-caspase inhibitor protects against noise-induced hearing loss in a rodent model - Yepes, Maria Fernanda; Minesinger, Kayla; Raciti, Federica M.; Salazar, Maria Camila; Rajguru, Suhrud M. (Frontiers in Neuroscience, 2025)
BackgroundDespite the high prevalence of noise-induced hearing loss (NIHL), no effective treatments exist currently. Underlying mechanisms behind NIHL include elevated reactive oxygen species and inflammation, all which ultimately lead to cellular apoptosis. Z-VAD-FMK, an apoptosis inhibitor, has demonstrated protective effects against cochlear hair cells exposed to ototoxic agents; however, its potential for treating NIHL remains unexplored. This study assessed the efficacy of Z-VAD-FMK as a therapeutic for noise-induced cochlear injury in a rodent model.MethodsRodents were assigned to one of four groups: (1) unexposed, (2) noise-exposed, (3) noise + vehicle, and (4) noise + Z-VAD-FMK. Noise delivery consisted of 1 h of 110 dB continuous white-noise, with Z-VAD-FMK administered intraperitoneally 6 h afterward. Auditory brainstem responses (ABRs), cochlear hair cell density, and protein levels were evaluated post-interventions.ResultsNoise exposure caused a permanent threshold shift across all frequencies, with minimal recovery by day 28. However, post-exposure treatment with Z-VAD-FMK significantly mitigated ABR threshold, amplitudes, and latencies shifts particularly at low and mid frequencies. Treatment rescued outer hair cells across middle and basal cochlear turns and reduced caspase-9 and IL-1β levels, as indicated by protein analysis.ConclusionOur findings indicate that a single intraperitoneal injection of Z-VAD-FMK can partially mitigate cochlear dysfunction induced by acoustic overexposure in a rodent model, highlighting its potential as a therapeutic intervention for NIHL.